2007
DOI: 10.1183/09031936.00165006
|View full text |Cite
|
Sign up to set email alerts
|

Trends in ethical and legal frameworks for the use of human biobanks

Abstract: Numerous studies of genetic epidemiology and post-genomics in respiratory diseases rely on the use of biobanks, defined as organised biological sample collections with associated personal and clinical data. The use of biobanks is increasing and raises several ethical issues. What are the ethical trends and legal frameworks in the post-genomic era? Are there new issues in relation to the developments of techniques and new study designs? How does this affect the clinician's attitudes and relationship with the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
204
0
13

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(218 citation statements)
references
References 47 publications
(46 reference statements)
1
204
0
13
Order By: Relevance
“…It is employed in the main studies with this design and represents new ethical and legal challenges. 5,6,12 In the ELSA-Brasil, the storage of genetic and cellular material, enabling access to DNA codes and to expression patterns of RNA and proteins, will allow testing associations between cellular and molecular alterations that precede the emergence of a series of diseases. New science fi elds that have just started to develop, called genomics and proteomics, will enable, in a future that is not so distant, a better prediction of chronic diseases that constitute public health problems in many countries, including Brazil.…”
Section: Continuementioning
confidence: 99%
“…It is employed in the main studies with this design and represents new ethical and legal challenges. 5,6,12 In the ELSA-Brasil, the storage of genetic and cellular material, enabling access to DNA codes and to expression patterns of RNA and proteins, will allow testing associations between cellular and molecular alterations that precede the emergence of a series of diseases. New science fi elds that have just started to develop, called genomics and proteomics, will enable, in a future that is not so distant, a better prediction of chronic diseases that constitute public health problems in many countries, including Brazil.…”
Section: Continuementioning
confidence: 99%
“…It has been suggested that special governance frameworks should be created to promote public trust (Caulfield et al, 2003;Cambon-Thomsen et al, 2007) and the UK Biobank established accordingly a separate ethics and governance council with this end in mind. Public trust is also believed to require different participatory approaches so that donors of tissue material should have control over how their specimens and data are used and for what purposes.…”
Section: In What Sense Is Public Trust At Stake?mentioning
confidence: 99%
“…22 The literature reveals widespread concern over the lack of guidance on these issues. [23][24][25] Yet to date, few studies have empirically examined how these ethical issues are being addressed, particularly with regard to genetic research with biological materials stored in biobanks. Focused examination of the publically available policies of biobanks is essential.…”
mentioning
confidence: 99%